2002
DOI: 10.3201/eid0808.010422
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Serogroup W135 Meningococcal Disease after the Hajj Pilgrimage, Europe, 2000

Abstract: The 2000 Hajj (March 15–18) was followed by an outbreak of Neisseria meningitidis W135 2a: P1.2,5 in Europe. From March 18 to July 31, 2000, some 90 cases of meningococcal infection were reported from nine countries, mostly the United Kingdom (UK) and France; 14 cases were fatal. Although most early cases were in pilgrims, the outbreak spread to their contacts and then to those with no known pilgrim contact. In France and the UK, the outbreak case-fatality rate was compared with the rate reported from national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(99 citation statements)
references
References 22 publications
4
95
0
Order By: Relevance
“…However, the first large MenW outbreak involving >400 cases from 16 countries due to a ST-11 cc strain was reported among the pilgrims attending the Hajj in Mecca in year 2000 (13,14). Subsequent sporadic cases were thought to be due to pilgrims returning from the Hajj and transmitting the infection to their close contacts, as have been reported in Europe (15). This clone has since spread to sub-Saharan Africa (16) and South America (17,18).…”
Section: Discussionmentioning
confidence: 98%
“…However, the first large MenW outbreak involving >400 cases from 16 countries due to a ST-11 cc strain was reported among the pilgrims attending the Hajj in Mecca in year 2000 (13,14). Subsequent sporadic cases were thought to be due to pilgrims returning from the Hajj and transmitting the infection to their close contacts, as have been reported in Europe (15). This clone has since spread to sub-Saharan Africa (16) and South America (17,18).…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies showed that W-135 and B were the commonest serogroups causing meningococcal meningitis (11,12). The risk of transmission increases owing to the fact that carriage may last between 5 and 15 weeks (13)(14)(15). In the study by Wilder-Smith et al, 15% of pilgrims were carriers of N. meningitidis following their return from pilgrimage, and interestingly 55% of these carriers tested positive during the next 6 months (16).…”
Section: Introductionmentioning
confidence: 99%
“…However, these pathogenic serogroups arise from a limited number of genetically defined clonal complexes that emerge and spread globally (Stephens, 1999). For example, W135 strains were known to be pathogenic but were not usually responsible for widespread outbreaks (Aguilera et al, 2002). Recently, novel W135 strains in the ST-11/ET-37 clonal complex have emerged and were responsible for worldwide meningitis outbreaks in pilgrims returning from the 2000 and 2001 Hajj pilgrimages and for regional outbreaks in 2002 and 2003 in Burkina Faso (Aguilera et al, 2002).…”
Section: Introductionmentioning
confidence: 99%